Thermal behavior of cellulose acetate produced from homogeneous acetylation of bacterial cellulose - Barud, Hernane S. [UNESP]; de Araujo Junior, Adalberto M. [UNESP]; Santos, Daniele B. [UNESP]; de Assuncao, Rosana M. N.; Meireles, Carla S.; Cerqueira, Daniel A.; Rodrigues Filho, Guimes; Ribeiro, Clovis Augusto [UNESP]; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Elsevier B.V., 2008)
Cellulose acetate (CA) is one of the most important cellulose derivatives and its main applications are its use in membranes, films, fibers, plastics and filters. CAs are produced from cellulose sources such as: cotton, sugar cane bagasse, wood and others. One promissory source of cellulose is bacterial cellulose (BC). In this work, CA was produced from the homogeneous acetylation reaction of bacterial cellulose. Degree of substitution (DS) values can be controlled by the acetylation time. The characterization of CA samples showed the formation of a heterogeneous structure for CA samples submitted to a short acetylation time. A more homogeneous structure was produced for samples prepared with a long acetylation time. This fact changes the thermal behavior of the CA samples. Thermal characterization revealed that samples submitted to longer acetylation times display higher crystallinity and thermal stability than samples submitted to a short acetylation time. The observation of these characteristics is important for the production of cellulose acetate from this alternative source. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: bacterial cellulose; homogeneous acetylation; cellulose acetate; thermal properties